The FREEDOM OF SPEECH AND EXPRESSION VS SOCIAL MEDIA VIOLATIONS - Arpana Bansal , Anita Rani (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to advancement of technology, people tend to use social media like Facebook, WatsApp, Twitter, Instagram, YouTube, etc. to read and share news and information. Social media is defined as a mobile- and web-based technology to create a social network in the virtual world through a collection of online communication channels. Social media technology made the world smaller because people from one part of the country can access information shared by a user from another. Freedom of expression is the right of every individual to hold opinions without interference and to seek, receive and impart information and ideas through any media—regardless of frontiers. In a democratic country like India, each and every citizen has the right to express and impart information through social media. Because we enjoy this freedom, we can upload, uplink, comment, like, share, etc. through social media. These social media sites provide complete or absolute freedom of expression; but as netizens how are we using it? This paper reviews the freedom of speech and expression and related violations through social media.